Medeni usul hukukunda fer’i müdahale etkisi - Özbaykal, Nagihan Tandoğan (My University, 2025)
Özellikle usul hukuku bağlamında çelişkili kararlar verilmesinin önlenmesi, yargıya güvenin sağlanması ve dolayısıyla hukuki güvenlik ilkesinin korunması, daha sonra açılması muhtemel davaların önlenmesi veya bu davalardaki yargılama süresinin azaltılması amaçlarına hizmet eden fer’i müdahale etkisi, geniş çerçevede fer’i müdahil ile ilk davanın asıl tarafı arasında görülen müteakip davada, ilk davada verilen hükmün bağlayıcı olması, bu hükmün ve gerekçesinde yer alan unsurların yanlış olduğunun ileri sürülememesi şeklinde ifade edilebilir. Fer’i müdahale etkisine ilişkin bu sonuç, Kanun’daki açık atıf sebebiyle ihbarın etkisi bakımından da kıyasen uygulanmaktadır. Fer’i müdahale etkisi, bir taraftan hükmün etkileri ile diğer taraftan üçüncü kişilerin yargılamaya katılımına ilişkin fer’i müdahale ve ihbar kurumları ile sıkı irtibat içindedir. Uygulamada sıklıkla başvurulan fer’i müdahale ve davanın ihbarı kurumlarının ortaya çıkardığı bu etki, daha önce tek başına akademik bir çalışmaya konu edilmemiş ve yargı kararlarında herhangi bir yönüyle yer almamıştır. Bu nedenle fer’i müdahale etkisinin tüm yönleriyle araştırılması ve değerlendirilmesi amacıyla bu çalışma yürütülmüştür. Bu çalışmada sırasıyla fer’i müdahale etkisinin esasları, amacı, şartları, konu-kişi-zaman bakımından kapsamı, dikkate alınma şekli, sınırlandırılması ve tarafların müdahale etkisi üzerindeki tasarrufları incelenmiştir. Çalışmanın tüm bölümlerinde ulaşılan sonuçlar, maddi hukukta müdahale etkisinin oluşabileceği örnek nitelikteki hukuki ilişkiler ve talepler üzerinden somutlaştırılmıştır. Hukukumuzda fer’i müdahale etkisine ilişkin düzenlemelerin kaynağı Alman Medeni Usul Kanunu’nun ilgili düzenlemeleridir. Bu nedenle çalışmanın tümü Alman hukuku ile karşılaştırmalı olarak yürütülmüştür. Fer’i müdahale etkisi İsviçre ve Avusturya hukukunda da geçerli olan bağlayıcı bir etki olduğundan İsviçre hukuku ve Avusturya hukukundaki düzenleme farklılıklarına ve görüşlere de değinilmiştir.

In the civil procedural law, the effect of the side intervention, which serves the purposes of preventing contradictory decisions, ensuring confidence in the judiciary and thus protecting the principle of legal certainty, preventing the filing of actions that may be filed later or reducing the duration of the proceedings in these cases, can be broadly defined as the fact that the judgment rendered in the first action is binding in the second action between the intervener and the main party of the first action, and that it cannot be argued that this judgment and the elements contained in its reasoning are wrongful. Due to the explicit reference in the Turkish Civil Procedure Code, this consequence regarding the effect of intervention is also applied by analogy in terms of the effect of third-party notice. The effect of intervention is in strong connection with the effects of the judgment on the one side, and the institutions of side intervention and third-party notice on the other side. The institutions of side intervention and third-party notice, which are frequently used in practice, give rise to this effect and this effect has not been the subject of an academic research on its own before and has not been included in judicial decisions in any aspect. For this reason, this research has been conducted in order to examine and evaluate the effect of side intervention in all aspects. In this research, the principles, purpose, conditions, (objective-subjective-temproal) scope, principle of taking into account, elimination or limitation and the dispositions of the parties on the effect of intervention are analyzed respectively. The conclusions reached in all sections of the research are concretized through examples of legal relationships and claims that may constitute an effect of intervention in substantive law. The relevant regulations of the German Code of Civil Procedure are the source of the regulations on the effect of side intervention in our law. Therefore, the entire research has been conducted in a comparative perspective with the German law. Since the effect of intervention is a binding effect that is also recognized in Swiss and Austrian law, the differences in the regulations and legal approaches in Swiss and Austrian law are also examined.
The effects of side intervention in civil procedure law
Keywords: Civil law; Davanın İhbarı; Effects of the Judgement; Fer’i Müdahale; Fer’i Müdahale Etkisi; Hükmün Etkileri Side Intervention Effect; İhbar Etkisi; Medeni hukuk; Side Intervention; Third-Party Notice; Third-Party Notice Effect; Turkey; Türkiye